Competence of SMK Teachers Based on Institutional Financial Accounting (SMK State in Pekanbaru) - Gusnardi, Gusnardi; Trisnawati, Fenny (Proceedings of the UR International Conference on Educational Sciences, 2018)
Financial accounting institutions are the new subjects taught at the vocational school. Based on observations through the Pekanbaru City MGMP Accounting, most of the teachers have not understood this material properly. Usually accounting teachers only teach financial accounting in general. For the competence of teachers in teaching these subjects, it needs to be analyzed, so that it can be known to what extent the teachers competence in teaching this material..This study sought to analyze the competence of accounting teacher at SMK Negeri Pekanbaru City-based financial accounting agencies. Data is obtained by distributing questionnaires related to professional competence regarding financial accounting institutions with 7 sub sections. Data processing and analysis is carried out using descriptive analysis for parts of competence in the institutions financial accounting material. The results showed that the competency of teachers in SMK Kota Pekanbaru in understanding the institutions financial accounting is still lacking when compared to their competence in teaching their usual financial accounting previously taught.It is necessary efforts so that the competence of the teachers about the financial accounting agencies can increase at least in proportion to their competence in teaching financial accounting.